(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to analyze the influence of leadership and business strategy on the performance of PT.SPM Jakarta. Data were collected through questionnaires and filled out by company employees, with a sample of 102 employees. The research method used is descriptive and verification. The data were processed and analyzed by using the partial hypothesis test (t test) using SPSS for window 20.0. The tool used in this study is multiple linear regression analysis, and the coefficient of determination at a significant level of 5%. The results of the study explain that the leadership variable is able to influence company performance, if the leadership is good, the performance will increase, the better the leadership felt by the employees, the better the company performance will be. Business strategy also has a positive effect on company performance and simultaneously leadership and business strategy have a positive effect on the performance of PT.SPM Jakarta.